Toxic Biological Effects Associated with Materials Used in Prosthodontics- A Survey - G.Swetha1 , Venkatesh Kommi2 , Keerthi Sasanka.L3 , Leslie Rani. S4 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Prosthodontics practice involves contact with restorative materials, auxiliary dental materials which arebroadly of different composition. The leakage and transfer of the potent allergic components from thesematerials is the cause of hypersensitive reactions to patients, dental professionals and the lab technicians.The biological side-effects of the materials that are in dental practice are rare. All artificial materials releasesubstances in the oral environment which are potent allergens that might cause side effects and adversereactions. The current study gives a statically about the dental professional knowledge and also makesthe aware of toxic biological side effects of these materials, also make them aware of the reporting of thecases. A cross sectional survey was conducted among 100 dental professionals about the Toxic Biologicaleffects associated with materials used in prosthodontics. Questionnaires with 20 close ended questions werecirculated among people. Results obtained analyzed using SPSS software.In this Study, almost 80% ofthem were aware that some components of the dental materials might cause a hypersensitivity reaction.57% of the participants have not experienced any allergic resin, latex, gloves etc.The prevalence of allergicreaction among Dental staff is low and most reported are due to latex, acrylate & formaldehyde. The presentstudy shows that there is a lack of knowledge on the toxic biological effects of dental material used inprosthodontics.